The evolution of the Brewer-Dobson circulation and the ozone layer during the last three decades - Ossó Castillón, Albert (Universitat de Barcelona, 2014)
In 1985 Joseph Farman and his colleagues of the British Antarctic Survey published a paper [Farman et al. 1985] showing that the total ozone content of the atmosphere during the Antarctic spring had decreased dramatically between 1975 and 1984. Subsequent studies confirmed this decrease and the term Antarctic ozone hole became popular. The occurrence of this phenomenon revitalized the interest of the climate community in the stratosphere. Since then many remarkable advances have been made in our understanding of stratospheric processes. These advances have been possible by the advent of remote sensing measurements of the atmosphere together with the sophistication of the atmospheric simulations. Nowadays it is known that stratospheric climate is determined by a complex coupling of dynamic, radiative and chemical processes.The view of the stratosphere as an isolated layer have changed completely and today it is widely accepted that both the tropospheric processes a.ect the stratospheric climate, and the other way around, the stratospheric processes a.ect the climate in the troposphere. Despite all the progresses made, our knowledge is far to be complete. There are still large uncertainties about how climate change is a.ecting the stratosphere and to what extent it will in.uence the stratospheric ozone recovery. Moreover recent studies [e.g., Thompson et al. 2012] evidenced that there are important discrepancies among observational data sets and between observations and numerical simulations of recent stratospheric temperature trends. OVERVIEW The aim of this thesis is to contribute on the understanding of the past evolution of the ozone layer and the Brewer-Dobson circulation. With this objective the following question will be addressed: 1. To what extent are the long-term trends of total ozone a.ected by the North Atlantic Oscillation (NAO) during winter and summer seasons? 2. How robust are the observed trends in the Brewer-Dobson Circulation (BDC)? 3. Is the current generation of coupled atmosphere-ocean ...